A THEOLOGICAL ANALYSIS OF SUICIDAL TERRORISM SAMSON’S TERRORISTS ACT ACCORDING TO JUDGES 16:30 - Yusak Tanasyah (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
This theological analysis delves into the complex and sensitive phenomenon of suicidal terrorism, drawing insights from the biblical narrative of Samson in Judges 16:30. By examining the life of Samson, a figure often cited in discussions surrounding violence and sacrifice, this paper seeks to explore the theological dimensions that may shed light on the motivations and justifications behind suicidal acts of terror. The study begins with examining the biblical text, particularly Judges 16:30, where Samson brings down the temple of the Philistines upon himself, resulting in his death. Through a careful exegetical analysis, we aim to uncover the theological underpinnings of Samson's actions and the implications for understanding contemporary instances of suicidal terrorism. The paper engages with theological concepts such as divine purpose, redemption, and sacrifice to explore how these themes manifest in the Samson narrative and their potential relevance to the ideological framework of modern terrorists. Additionally, it considers the ethical and moral implications of such acts within a theological context, seeking to distinguish between legitimate expressions of faith and distorted interpretations that lead to violence. By bridging biblical scholarship with contemporary issues, this theological analysis aims to contribute to a nuanced understanding of the theological roots of suicidal terrorism. It encourages a dialogue that acknowledges the complexities inherent in interpreting religious texts and their potential impact on individuals and communities grappling with issues of violence and extremism